Islam in the Eyes of the West : Images and Realities in an Age of Terror - Edited by Tareq Y. Ismael & Andrew Rippin; Series Editor: Anoushiravan Ehteshami (London Routledge Taylor and Francis Group, 2010)
From the terrorist attacks of September 11, 2001, in New York to the Madrid and London bombings of 2004 and 2005, the presence of Muslim communities in the West has generated security issues and major political concern. Governments, the media, and the general public have raised questions regarding potential links between Western Muslims, radical islam and terrorism.
Include Index
Keywords: Islam--Public opinion -- Terrorism--Religious aspects--Islam -- Interfaith relations